Mechanical properties of concrete with recycled aggregate and M−sand. (2021) - Surendar, M.; Beulah Gnana Ananthi, G.; Sharaniya, M.; Deepak, M.S.; Soundarya, T.V.
Abstract: The suitability of replacement of natural aggregate (NA) with recycled aggregate (RA) mainly depend on the properties of recycled aggregates. This experimental study provides the mechanical and durability properties of recycled aggregate concrete (RAC) as compared to those of the conventional normal aggregate concrete (NAC). Seven mixes of concrete were casted using normal and recycled coarse aggregate and tested with different RCA replacement percentages of 0%, 10%, 15%, 20%, 25%, 50% and 75% respectively. The development of cube compressive strength, cylinder split tensile strength at 7 and 28 days and water absorption are reported. Therefore, with optimal replacement of RA, the mechanical and durability properties of concrete mixtures can be improved, reducing the detrimental effects of RA from the environment.